Cybersecurity and risk behaviour on mobile individual consumers in Spain - Carlos Martínez de Ibarreta; Covadonga Gijón (International Telecommunications Society (ITS), 2016)
Nowadays a big and increasing proportion of world's population uses Internet in their day life and web connection via mobile is having a growing importance. Day by day there is more information about the risks and dangers of a misuse of Internet and mobile phones, which may involve all sorts of negative consequences, from computer malfunction to economical or personal damages. Almost 30% of Spanish mobile users acknowledge to have suffered any kind of mobile security incident during the last three months, whereas roughly 20% of them acknowledge to have suffered any kind of fraud via mobile. Consequently, a significant fraction of users has been victim of some kind of cyber-attacks. In this paper it is observed, among others, positive relationship between level of security measures and level of attacks or frauds. There are two possibilities: the risk compensation theory or protection after an attack or fraud.
Keywords: 330; cybersecurity; mobile; cyber-attacks; fraud; behaviour